(untitled) (Indian Journal of Public Health Research & Development, 2026)
Background: Clinical trials have traditionally been framed as experimental tools rather than therapeutic options, and the doctor–patient relationship has largely been paternalistic. The emergence of precision medicine and the shift toward patient-centred care challenge this dichotomy, suggesting that clinical trials could be considered part of routine treatment pathways. Methods: A narrative synthesis of published literature was conducted to examine patient and physician perspectives on clinical trials when offered as treatment choices. Evidence was analysed to identify key motivators, barriers, and areas of alignment and divergence between patients and physicians. Results: Patients value access to advanced therapies, close monitoring, and a sense of hope, while physicians emphasise therapeutic innovation and ethical responsibility. Barriers include therapeutic misconception, limited clinician awareness, workload constraints, and logistical challenges. Despite these obstacles, both groups support transparent discussion of clinical trials within clinical care. Conclusion: Integrating clinical trials into treatment frameworks, with informed patients and physicians, ethical safeguards, and institutional support, can make them a legitimate and patient-centred treatment option.